A Comparative Study of The Indonesian Economy During Covid-19 (2019-2021) and Post Covid-19 (2022-2024): 1. Introduction, 2. Literature Review, 3. Methodology of Study, 4. Findings and Discussion, 5. Conclusions and Suggestions, References - NABILA, JIHAN; Yusnida (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze in more depth the differences in economic growth, poverty, unemployment, and inflation in Indonesia during and post the covid-19 pandemic, as well as analyze the policies that have been implemented. This research uses quantitative methods with secondary data for the period of the covid-19 pandemic (2019-2021) and post the covid-19 pandemic (2022-2024). The variables used are economic growth, unemployment, poverty, and inflation. This study uses the Shapiro Wilk normality test and the Paired Sample T-Test. The results showed that economic growth, poverty rate, unemployment, and inflation during and post the covid-19 pandemic remained stable and did not experience significant differences. This stability can be attributed to various government policies aimed at reducing the negative impact of the pandemic. Nevertheless, some of these sectors are still adjusting, even though the pandemic is over. The policies implemented during the pandemic have proven to be effective in mitigating the long-term negative impacts, so that economic conditions remain under control after the pandemic. For future research, it is recommended that the analysis be extended to the regional level to get a clearer picture of the differences in economic recovery. Furthermore, a long-term analysis is needed to see the impact of the pandemic on the Indonesian economy in the next few years, to understand the recovery trend or new challenges that may arise after the pandemic.